Differences in Lesbian, Bisexual, and Heterosexual Women’s Experiences of Sexual Assault and Rape in a National U.S. Sample - Canan, Sasha N. (Journal of interpersonal violence, 2021)
Lesbian and bisexual women experience significantly higher rates of sexual assault and rape compared with heterosexual women. Despite this, researchers have yet to distinguish whether sexual orientation itself or some other related social characteristics explain these higher rates. The objective of this study was to analyze women’s rates of sexual assault and rape across sexual orientation status while accounting for other social characteristics (e.g., race, education, income, outness). Women (N = 1,366), who identified as lesbian (31%), bisexual (32%), and heterosexual (31%), completed a nationally distributed, cross-sectional online survey in 2016. Victimization and repeat victimization were assessed using a modified version of Sexual Experience Survey–Short Form Victimization. Overall, 63% of bisexual, 49% of lesbian, and 35% of heterosexual women reported experiencing rape in their lifetime. When holding all other social characteristics constant, sexual orientation remained a significant predictor in the model. Compared with the odds of heterosexual women experiencing sexual assault or rape, bisexual women (3.7 odds of victimization; 7.3 odds of repeat victimization) and lesbian women (3.2 odds of repeat victimization) were disproportionately victimized. Sexual orientation clearly plays a role in sexual victimization risk, independent of other measured sociodemographic indicators. Continued research is needed to explore possible mechanisms behind sexual assault and rape prevalence, as well as the influence of contextual factors of victimization risk among sexual minority men.